In Pursuit of Equity: Women, Men, and the Quest for Economic Citizenship in 20th Century America - Brooks, Tequila J. (Relations Industrielles / Industrial Relations, 2003)
The article reviews the book, "In Pursuit of Equity: Women, Men, and the Quest for Economic Citizenship in 20th Century America," by Alice Kessler-Harris.
Keywords: 20th century; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Economic conditions; Employment policies; History; Labor Unions; Labor law; Legal status laws etc; Men; Rights; Women